Tonight Show dan Humorously Masculine - Johari Saputra; Sumekar Tanjung (Jurnal Mahasiswa Komunikasi Cantrik, 2021)
Television is a form of development of information and communication technology media. Television broadcasts various programs, including the Tonight Show. Television broadcasts various programs, including the Tonight Show. The Tonight Show that was brought by Vincent and Desta was able to present funny and entertaining humor. Vincent and Desta always look masculine in every episode. This study aims to find out how the masculinity of Vincent and Desta's humor is displayed on the Tonight Show. The study used qualitative analysis. The results showed that Vincent and Desta's humorous masculinity was displayed with cognitive and affective differences in men, and humorous masculinity was displayed in affiliative (positive) and aggressive (negative) forms.Keywords: Television, Tonight Show, Semiotics, Humor, Masculinity